Towards developing smart environment using wireless sensor and ad hoc networks - Pathan, Al-Sakib Khan; Hong, Choong Seon; Lee, Hyung-Woo (2006)
The miniaturization process of various sensing devices has become a reality by enormous research and advancements accomplished in MEMS (Micro Electro-Mechanical Systems) and VLSI (Very Large Scale Integration) lithography. With the advancements of such optimization techniques for hardware, algorithms, and protocols for networking, various wireless technologies have also emerged. The attractive features of these modern technologies have attracted many researchers to work on the design, application and utilization of systems benefited by these high-tech equipments. As a consequence, the idea of smart environment has been come into vision. The focus of this paper is to propose a framework for developing a smart environment aided with the wireless technologies which not only aims at smartening the surrounding environment but also could facilitate the use of a number of smart systems.